2024
DOI: 10.18632/aging.205445
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a basement membrane gene signature for predicting prognosis and estimating the tumor immune microenvironment in prostate cancer

Tao Xie,
Du-Jiang Fu,
Kang-Jing Li
et al.

Abstract: Basement membrane plays an important role in tumor invasion and metastasis, which is closely related to prognosis. However, the prognostic value and biology of basement membrane genes (BMGs) in prostate cancer (PCa) remain unknown. In the TCGA training set, we used differentially expressed gene analysis, protein-protein interaction networks, univariate and multivariate Cox regression, and least absolute shrinkage and selection operator regression to construct a basement membrane-related risk model (BMRM) and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…BM invasion is pivotal for tumor metastasis (Chang and Chaudhuri 2019), spotlighting the significance of BM-related genes (BMGs) in cancer research. Studies have shown that models based on BMGs effectively predict outcomes and immunotherapy impacts in solid tumors like lung adenocarcinoma (Zhang et al 2023), pancreatic cancer (Zhou et al 2024), and prostate cancer (Xie et al 2024). In 2023, Sun W et al (Sun et al 2023) developed a prognostic model for HCC using BMGs, aiding clinicians in prognosis assessment and guiding immunotherapy and medication choices.…”
Section: Introductionmentioning
confidence: 99%
“…BM invasion is pivotal for tumor metastasis (Chang and Chaudhuri 2019), spotlighting the significance of BM-related genes (BMGs) in cancer research. Studies have shown that models based on BMGs effectively predict outcomes and immunotherapy impacts in solid tumors like lung adenocarcinoma (Zhang et al 2023), pancreatic cancer (Zhou et al 2024), and prostate cancer (Xie et al 2024). In 2023, Sun W et al (Sun et al 2023) developed a prognostic model for HCC using BMGs, aiding clinicians in prognosis assessment and guiding immunotherapy and medication choices.…”
Section: Introductionmentioning
confidence: 99%